Dampak pengelolaan limbah sampah pada penghawaan, kenyamanan terhadap pengguna pada bangunan pasar tradisional kranji baru - Abdillah, Fahrul; Zulkarnain (Jurnal Ilmiah Arjouna: Architecture and Environment Journal of Krisnadwipayana, 2024)
Waste management in Bekasi Regency is still done conventionally through containerization, collection, transportation, and final disposal (Negara, 2020). Traditional markets contribute around 24% of the total waste, dominated by organic and inorganic waste. Kranji Baru traditional market faces obstacles such as limited treatment facilities, low user awareness, as well as the less strategic location of Temporary Storage Sites (TPS). This study analyzes the impact of waste management on air quality and user comfort (Waluyo & Pramitasari, 2023) and identifies factors that influence its effectiveness. This research uses a mixed-method method with quantitative and qualitative approaches. Measurements of temperature, humidity, and waste volume were conducted quantitatively, while observations and interviews with traders and visitors were conducted qualitatively. The study results show that the market produces an average of 1.5 tons of waste per day with a composition of 60% organic and 40% inorganic. Waste is transported twice a day, but the separation and treatment system is still not optimal. The location of the TPS on the edge of the main road causes odor pollution that disturbs users' comfort. In addition, the lack of ventilation increases humidity to 75%-85% and the market temperature reaches 30°C - 33°C, higher than the surrounding environment. 65% of visitors complained about the odor of waste, while 40% of vendors stated that high humidity affected the quality of their wares. Recommendations for this study include separation of waste at source, education for market users, relocation of TPS to a strategic location with a closed system, and improvement of ventilation and drainage systems to improve the comfort of market users.